2013
DOI: 10.1016/j.biomaterials.2013.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced vaginal drug delivery through the use of hypotonic formulations that induce fluid uptake

Abstract: Mucosal epithelia use osmotic gradients for fluid absorption and secretion. We hypothesized that administration of hypotonic solutions would induce fluid uptake that could be advantageous for rapidly delivering drugs through mucus to the vaginal epithelium. We found that hypotonic formulations markedly increased the rate at which small molecule drugs and muco-inert nanoparticles (mucus-penetrating particles, or MPP), but not conventional mucoadhesive nanparticles (CP), reached the vaginal epithelial surface in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 39 publications
6
65
0
Order By: Relevance
“…Animal studies using fluorescent labeling and histologic imaging enable a more direct assessment of mucosal coverage. 34 These studies indicate optimal mucosal coverage with isoosmolar and slightly hypotonic products. Finally, none of these methods addresses diffusion of drug or HIV into the mucosal tissue over time.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies using fluorescent labeling and histologic imaging enable a more direct assessment of mucosal coverage. 34 These studies indicate optimal mucosal coverage with isoosmolar and slightly hypotonic products. Finally, none of these methods addresses diffusion of drug or HIV into the mucosal tissue over time.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticle size was characterized using dynamic light scattering (90° scattering angle), and ζ-potential was determined via laser Doppler anemometry with a Zetasizer Nano ZS90 (Malvern Instruments, Southborough, MA) (Table S1). We have previously found that a near-neutral ζ-potential for these particles indicates that the surface is sufficiently coated with PEG to rapidly penetrate human cervicovaginal mucus (Table S1) [22]. All measurements were performed at 25°C and according to instrument settings.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the administration of mucus-penetrating NPs in a hypotonic vehicle (water) was able to enhance mucus transport. This effect was presumably related with improved particle trafficking towards the mucosa as driven by osmotic pressure [79]. Data obtained in vivo by other groups further materialized the potential of densely PEG-modified nanocarriers in improving vaginal distribution [81][82].…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…In this last case, differences in mucus samples and PEGylation protocols may justify contradictory data. The potential value of densely PEG-modified NPs in improving vaginal distribution of nanocarriers or nanosized drugs, including at collapsed mucosal folds, has been further demonstrated by Hanes and collaborators in both ex vivo [77] and animal in vivo [78][79][80] experiments. In particular, the administration of mucus-penetrating NPs in a hypotonic vehicle (water) was able to enhance mucus transport.…”
Section: Accepted Manuscriptmentioning
confidence: 90%